EUS-Guided versus Percutaneous Image-Guided Liver Biopsy: A Battle for Supremacy! - Mishra, Shubhra; Bush, Nikhil; Rana, Surinder S. (Journal of Digestive Endoscopy, 2021)
Liver biopsy has been the gold standard investigation for diagnosing and staging liver diseases. Image-guided percutaneous liver biopsy is a time-tested technique for obtaining the liver tissue in diffuse liver diseases. However, it is contraindicated in patients with ascites, altered mental status, skin infections, coagulopathy, and thrombocytopenia. It is associated with adverse events including postprocedure pain, bleeding, and pneumothorax. Transvenous liver biopsy can be performed in most cases with these contraindications, but it is an expensive technique and has its own inherent risks. Endoscopic ultrasound (EUS)-guided liver biopsy (EUS-LB) is a relatively new technique that has shown promising results and seems to have a potential of replacing percutaneous liver biopsy. In this news and views, we discuss the results of a randomized controlled trial (RCT) comparing EUS-guided and percutaneous techniques of liver biopsy. This RCT reported that percutaneous technique is superior in terms of diagnostic adequacy and total expenditure without any significant adverse effects compared with EUS-LB. EUS-LB is a promising technique that needs to be further explored in terms of appropriate situations in which it can be preferred over percutaneous or transvenous routes.
Keywords: endoscopic ultrasound; liver biopsy; ultrasound; bleeding